Una versión polémica de La Celestina.: La adaptación de Michel Garneau traducida para la escena española - Bastianes, María (Talía. Revista de estudios teatrales, 2021)
This article examines Michel Garneau’s French Canadian adaptation of La Celestina (Célestine là-bas près des tanneries au bord de la rivière) as well as the subsequent controversial translation prepared by Álvaro García Meseguer for Robert Lepage’s Spanish production (2004). I begin with a detailed analysis of the translated text, a vital prerequisite for the subsequent discussion of its limitations as well as its contributions to the performance history of Fernando de Rojas’s text on the Spanish stage. In order to achieve this goal, I have employed a multimodal theoretical approach based on José Luis García Barrientos’ methodology for the study of dramatic texts, alongside María Rosa Lida de Malkiel’s description of theatrical devices employed in La Celestina and José Romera Castillo quantitative analysis of Gonzalo Torrente Ballester’s 1988 adaptation.